Drug-resistant tuberculosis and advances in the treatment of childhood tuberculosis. Issue 1 (December 2016) - Seddon, James; Schaaf, H.
Abstract Over the last 10 years, interest in pediatric tuberculosis (TB) has increased dramatically, together with increased funding and research. We have a better understanding of the burden of childhood TB as well as a better idea of how to diagnose it. Our appreciation of pathophysiology is improved and with it investigators are beginning to consider pediatric TB as a heterogeneous entity, with different types and severity of disease being treated in different ways. There have been advances in how to treat both TB infection and TB disease caused by both drug-susceptible as well as drug-resistant organisms. Two completely novel drugs, bedaquiline and delamanid, have been developed, in addition to the use of older drugs that have been re-purposed. New regimens are being evaluated that have the potential to shorten treatment. Many of these drugs and regimens have first been investigated in adults with children an afterthought, but increasingly children are being considered at the outset and, in some instances studies are only conducted in children where pediatric-specific issues exist.